2007
DOI: 10.1086/517951
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Genetic Diversity of Methicillin-ResistantStaphylococcus aureusStrains in Residential Care Homes for Elderly Persons in Hong Kong

Abstract: This study documented the emergence of SCCmec types IV and V among genetically diverse MRSA strains in residential care homes for elderly persons in Hong Kong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…There were 74 SCCmec type III and 14 SCCmec type II isolates detected in this study. SCCmec type III is the prevalent SCCmec type of MRSA clinical strains in China [19]. Antibiogram analysis showed that overall, the type II and type III isolates demonstrated resistance to more antimicrobials than the type IV isolates.…”
Section: Discussionmentioning
confidence: 99%
“…There were 74 SCCmec type III and 14 SCCmec type II isolates detected in this study. SCCmec type III is the prevalent SCCmec type of MRSA clinical strains in China [19]. Antibiogram analysis showed that overall, the type II and type III isolates demonstrated resistance to more antimicrobials than the type IV isolates.…”
Section: Discussionmentioning
confidence: 99%
“…In general, nursing home residents are colonized with hospital-acquired MRSA, typically SCC mec II. However, reports of CA-MRSA in nursing homes are slowly emerging [25][26][27][28][29]. In San Francisco, California, 12 (3.8%) of 318 CA-MRSA clinical isolates originated from nursing homes [25].…”
Section: Discussionmentioning
confidence: 99%
“…A cluster of infections due to SCCmec V MRSA was noted in 5 of 76 residents in a nursing home in Finland [29], and another nursing home in Germany reported that 7.6% of 197 residents were found to be colonized with PVL-containing MRSA strains [28]. A study of 949 residents in residential and continuum care facilities in Hong Kong noted that 23 (2.4%) were colonized with SCC mec IV or V MRSA strains [27]. In our study, 8 MRSA-colonized residents (9%) were colonized with SCCmec IV strains, including 2 residents who were colonized with PVLpositive strains, suggesting spread of CA-MRSA into southeastern Michigan nursing homes.…”
Section: Discussionmentioning
confidence: 99%
“…Multiplex PCRbased accessory gene regulator (agr) grouping was performed using the primer sets for agr groups IeIV. 11,12 Multilocus sequence typing (MLST) was performed on representative strains for each unique spa type and agr group combination. Strains with the same spa type and agr group results were used to infer MRSA clones.…”
Section: Molecular Analysismentioning
confidence: 99%